1979
DOI: 10.1029/rg017i005p01021
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic solar cosmic rays

Abstract: This paper reviews the present state of knowledge concerning the relativistic particles of solar origin. The analytic techniques for obtaining information regarding the distribution of particles in the interplanetary space from ground‐based observations are described. The general features of pitch angle anisotropy of high‐energy particles are outlined. The concepts of relativistic particle propagation in the corona and interplanetary space are discussed with special reference to the relevant new ideas that hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
2

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 143 publications
2
69
0
2
Order By: Relevance
“…It is concluded that the observed higher frequency wiggles in atmospheric "C/12C ratios occurring with time scales of about two hundred years and of 1 to 2 percent in magnitude (de Vries, 1958; Suess, 1970a,b;1979;Damon, Lerman, and Long, 1978), are largely due to solar activity dependent modulation of the galactic cosmic ray flux by solar plasma. These variations override a slowly varying sinusoidal change of about 10 percent in magnitude during the last approximately 8000 years, which is believed to be primarily due to changes in the geomagnetic field.…”
mentioning
confidence: 99%
“…It is concluded that the observed higher frequency wiggles in atmospheric "C/12C ratios occurring with time scales of about two hundred years and of 1 to 2 percent in magnitude (de Vries, 1958; Suess, 1970a,b;1979;Damon, Lerman, and Long, 1978), are largely due to solar activity dependent modulation of the galactic cosmic ray flux by solar plasma. These variations override a slowly varying sinusoidal change of about 10 percent in magnitude during the last approximately 8000 years, which is believed to be primarily due to changes in the geomagnetic field.…”
mentioning
confidence: 99%
“…Up until July 2017, some 71 GLEs had been measured as illustrated in Figure 1, the maximum increases as points together with a smoothed plot of the sunspot number, which is a commonly accepted measure of solar activity. The ionisation chamber data have been normalised to high latitude neutron monitor data [14], while the latter are obtained from [15]. Sea-level monitors have been used but the partial geographic coverage afforded by the available monitors at any given time means that there could have been larger increases at other locations.…”
Section: Ground Level Enhancementsmentioning
confidence: 99%
“…GLEs have been recorded and analysed since 1942, and are numbered sequentially (12). With the exception of GLE5 (February 1956), of the 64 GLEs observed up to 2003, none has presented any risk of attaining an annual dose of 1 mSv (the ICRP recommended public exposure limit) (29).…”
Section: Solar Flaresmentioning
confidence: 99%